Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak Dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Jakarta Selatan (Studi kasus pada wajib pajak kendaraan bermotor di samsat Jakarta Selatan) - Supiyanti; Romenah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to test the influence of tax awareness, tax sanctions, and the quality of tax services on the compliance of motor vehicle taxpayers in the South Jakarta Samsat. This study uses a quantitative method with the type of research of taxpayers who own motor vehicles in Samsat South Jakarta with a sample of 100 respondents using the Slovin formula, data obtained using interviews and distributing questionnaires and documenting them at Samsat South Jakarta and data obtained were analyzed using spss statistics 27 of 2025 with validity, reliability, classical assumption test and multiple linear regression test. The results of the study show that taxpayer awareness, tax sanctions, and the quality of tax services have a positive and significant effect on the compliance of motor vehicle taxpayers both partially and simultaneously. Suggestions for the government to continue to improve the quality of services so that and for future researchers, it is recommended to add other variables.